Influence of Tool Geometry on the Quality and Mechanical Properties of FSW Weldment for Al-alloy (7020-T53) - Jweeg, Muhsin Jaber; Tolephih, Moneer Hameed; Abdul-Sattar, Muhammed (Nahrain University College of Engineering Journal, 2014)
In this paper the influence of toolgeometry and welding parameters(rotating speed and travel speed) on thequality and mechanical properties byusing friction stir welded joints for(7020-T53) aluminum alloy.Three types of tool geometry variableswere used ( pin, shoulder and shoulderinclination), internal defect (tunnel) wasdetected by using X-Ray radiography forall samples which are welded at weldingparameters (rotating speed and travelspeed), perfect tool geometry that givesdefect free was by increasing pindiameter with threaded ,increasingshoulder diameter and shoulderinclination (2o) for safety purposeradiography test was also performed toexamine defect free of weldments(increasing tool dimensions and pinthreaded gives increasing stir and heatinput).The effect of welding parameters(rotation and travel speed) using toolgeometry that gives defect free wereinvestigated using different mechanicaltests including (tensile, bending andmicrohardness). Macro andmicrostructure change during (FSW)process were studied and differentwelding zones were investigated usingoptical microscope. Based on the frictionstir welding experiments conducted inthis study the result show that aluminumalloy (7020-T53) can be welded usingFSW process, the optimum weldingparameters 1400rpm rotational toolspeed and 40mm/min travel speed whichgive the maximum welding efficiency(83%), increasing rotational speed themicrohardness increases in weld zonedue to decreasing the grain size.